2008
DOI: 10.1029/2008gc002102
|View full text |Cite
|
Sign up to set email alerts
|

New absolute paleointensity results from the Parana Magmatic Province (Uruguay) and the Early Cretaceous geomagnetic paleofield

Abstract: Thellier paleointensity experiments are carried out on the Early Cretaceous Arapey Formation, which belongs to the Parana Magmatic Province (PMP) in northern Uruguay. Twenty‐seven samples out of 225 analyzed yield reliable absolute intensity determinations. For these samples the NRM fraction f used for determination ranges between 0.33 to 0.83 and the quality factor q ranges from 4.5 to 14.1, being generally greater than 5. The flow‐mean paleointensity values obtained in this study range from 16.3 ± 2.3 to 41.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
4
9
0
Order By: Relevance
“…Globally, early Cretaceous paleointensities appear similar to the Brunhes data. This reinforces some previous suggestions (Goguitchaichvili et al, 2002(Goguitchaichvili et al, , 2008 about the invalidity of the Mezozoic Dipole Low hypothesis (Prévot et al, 1990). High geomagnetic intensities have been reported (Tarduno et al, 2001(Tarduno et al, , 2002 for Early Cretaceous, which are consistent with some inferences from computer simulations (Glatzmaier et al, 1999).…”
Section: 3 P a L E O I N T E N S I T Ysupporting
confidence: 89%
See 2 more Smart Citations
“…Globally, early Cretaceous paleointensities appear similar to the Brunhes data. This reinforces some previous suggestions (Goguitchaichvili et al, 2002(Goguitchaichvili et al, , 2008 about the invalidity of the Mezozoic Dipole Low hypothesis (Prévot et al, 1990). High geomagnetic intensities have been reported (Tarduno et al, 2001(Tarduno et al, , 2002 for Early Cretaceous, which are consistent with some inferences from computer simulations (Glatzmaier et al, 1999).…”
Section: 3 P a L E O I N T E N S I T Ysupporting
confidence: 89%
“…The Posadas Formation mean paleointensity agrees reasonably well with values from the coeval Arapey and Serra Geral Formations (Goguitchaichvili et al, 2008) while the slightly older Ponta Grossa dikes yielded relatively lower geomagnetic field strength. This suggests high geomagnetic intensities for the Early Cretaceous reinforcing some previous suggestions (Goguitchaichvili et al, 2002(Goguitchaichvili et al, , 2008 about the invalidity of the Mezozoic Dipole Low hypothesis (Prévot et al, 1990).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this section we will only recall some main results of our rock-magnetic experiments since these samples were already partly investigated by Goguitchaichvili et al (2008). The susceptibility vs. temperature experiments indicates, in most cases, the presence of Ti-poor titanomagnetites.…”
Section: Principal Results Of Magnetic Measurementsmentioning
confidence: 98%
“…In this study, we present new detailed rock-magnetic and paleomagnetic directional data from 35 lavas (302 standard paleomagnetic cores) sampled in the Central-Northern region of Uruguay in order to contribute to both paleosecular variation of Earth's magnetic field during early Cretaceous and paleomagnetic pole positions for the stable south America. This work comes to complete the reconnaissance paper (first sample collection campaign in Uruguay in 2005) of Goguitchaichvili et al (2008). These authors reported five absolute paleointensity results and no directional data.…”
Section: Introductionmentioning
confidence: 93%